Nanosponges for advanced drug delivery - Yapa, Asanka Sajini (Kansas State University, 2017)
A novel type of supramolecular aggregate, named "nanosponge" was synthesized through the interaction of novel supramolecular building blocks with trigonal geometry. The cholesterol-(K/D)[subscript n]DEVDGC)₃-trimaleimide unit consists of a trigonal maleimide linker to which homopeptides (either K or D) of variable lengths (n = 5, 10, 15, 20) and a consensus sequence for executioner caspases (DEVDGC) are added via Michael addition. Upon mixing in aqueous buffer, cholesterol-(K)[subscript n]DEVDGC)₃-trimaleimides, as well as a 1:1 mixture of cholesterol-(K/D)[subscript n]DEVDGC)₃-trimaleimides form stable nanosponges, whereas cholesterol-(D)[subscript n]DEVDGC)₃-trimaleimide is unable to form supramolecular aggregates by itself. The structure of the novel nanosponges was revealed through explicit solvent and then coarse-grained molecular dynamics (MD) simulations. The nanosponges are between 80nm and several micrometers in diameters and virtually non-toxic to monocyte/macrophage-like cells. Furthermore, the structure of novel binary nanosponges consisting of cholesterol-(K/D)[subscript n]DEVDGC)₃-trimaleimide units possessing a trigonal maleimide linker, to which either lysine (K)₂₀ or aspartic acid (D)₂₀ are tethered, has been elucidated by means of TEM. A high degree of agreement between these findings and structure predictions through explicit solvent and then coarse-grained molecular dynamics (MD) simulations has been found. Based on the nanosponges’ structure and dynamics, caspase-6 mediated release of the model drug 5(6)-carboxyfluorescein has been demonstrated. Moreover, the binary (DK20) nanosponges have been found virtually non-toxic in cultures of neural progenitor cells. Additionally, DK20 nanosponges were taken up efficiently by leucocytes (WBC) in peripheral blood within 3h of exposure. The percentage of live cells among the WBC was not significantly decreased by the DK20 nanosponges. Therefore, this novel material holds great promise for improved cell-mediated therapy. Two different nanosponges loaded with the anticancer agent perillyl alcohol (POH) were developed to test the suitability of nanosponges for cell-based cancer therapy. Drug-loaded nanoshuttles featuring trigonal supramolecular building blocks, type (D-POH)₁₀K₂₀ and (D-POH)₁₀R₂₀ were synthesized, purified, and characterized by Dynamic Light Scattering (DLS) and Atomic Force Microscopy (AFM). They were then tested in cell cultures of murine glioma cells (GL26) and murine neural progenitor cells (NPC). The two nanosponges exhibited significantly different biophysical properties (size distribution and zeta potentials). Consequently, different efficacies in killing GL26 and NPC were observed in both, serum free and serum containing culture media. The results from these experiments confirmed that type (D-POH)₁₀K₂₀ nanosponge is an excellent candidate for the cytotherapy of glioblastoma.
Keywords: Nanosponges; Drug delivery; Oligopeptides